Plant-Derived Toxin Inhibitors as Potential Candidates to Complement Antivenom Treatment in Snakebite Envenomations - Adrião, Asenate A. X.; dos Santos, Aline O.; de Lima, Emilly J. S. P.; Maciel, Jéssica B.; Paz, Weider H. P.; da Silva, Felipe M. A.; Pucca, Manuela B.; Moura-da-Silva, Ana M.; Monteiro, Wuelton M.; Sartim, Marco A.; Koolen, Hector H. F. (Frontiers in Immunology, 2022)
Snakebite envenomations (SBEs) are a neglected medical condition of global importance that mainly affects the tropical and subtropical regions. Clinical manifestations include pain, edema, hemorrhage, tissue necrosis, neurotoxic signs, and may evolve to functional loss of the limb, acute renal, respiratory failure, and even death. The standard treatment for snake envenomations is antivenom, which is produced by the hyperimmunization of large animals with snake toxins. The inhibition of the effects of SBEs using natural or synthetic compounds has been suggested as complementary treatments particularly before hospital admission for antivenom treatment, since these molecules are able to inhibit toxins. Biodiversity-derived molecules, namely those extracted from medicinal plants, are promising sources of toxin inhibitors aiming to minimize the deleterious consequences of SBEs. In this review, we systematically synthesize the literature on plant metabolites that are toxin-inhibiting agents, as well as present the potential mechanisms of action of molecules derived from natural sources. These findings aim would help to understand the potential that natural products have to provide new lead compounds that may represent new possibilities in ancillary therapy for the treatment of this neglected condition.